Levels of Processing Effects on Memory for Color-Object Associations - Mirela Dubravac; Chhavi Sachdeva; Nicolas Rothen (Journal of Cognition)
The levels of processing effect demonstrates that deeper encoding (processing meaning) enhances memory retention more than shallow encoding (processing perceptual features). While extensively studied with verbal materials, limited research has addressed this effect using nonverbal materials such as pictures. Previous studies have used pleasantness judgments to induce deep encoding and judgments of straight lines to induce shallow encoding. However, these tasks confound level of processing with other factors like task relevance, self-reference, and attentional scope, offering alternative explanations for observed memory performance differences. This online study (N = 307) tested the levels of processing framework for pictures using novel encoding tasks to isolate the effect of semantic processing. The novel encoding tasks involved a size judgment. In the shallow encoding condition, participants compared the size of an object to the displayed size of a reference object presented on the screen. This is a perceptual comparison of two pictures. In the deep encoding condition, participants compared the size of an object to the real-life size of a reference object. This requires an understanding of the semantic meaning of the presented object. Our results showed better memory performance in deep encoding conditions (pleasantness judgment, real-life size judgment) than shallow encoding conditions (line judgment, displayed size judgment), supporting the levels of processing framework. Additionally, the new size judgment tasks minimized alternative explanatory factors, providing a clearer understanding of how semantic processing influences visual associative memory. These findings confirm the applicability of the levels of processing effect to nonverbal materials.